2020
DOI: 10.4103/jfmpc.jfmpc_490_20
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and awareness of varicose veins among teachers in Abha, Saudi Arabia

Abstract: Background: Teachers, compelled by the nature of their profession, are required to stand for a significant amount of time. This prolonged standing, being one of the risk factors for venous insufficiency, puts them at risk to develop varicose veins. Hence, as there is a need to educate and sensitize the teachers. This study was carried out to investigate the prevalence and awareness regarding varicose veins in school teachers. Methods: A cross sectional, questionnaire ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…In Saudi Arabia, a study was done in Jeddah, Dammam, Makkah revealed that the prevalence of VV among females from the general population was 66% [ 18 ]. Another study done in Abha investigated the prevalence of VV among school teachers of both genders and reported a high prevalence of 42%; most of them were female teachers [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Saudi Arabia, a study was done in Jeddah, Dammam, Makkah revealed that the prevalence of VV among females from the general population was 66% [ 18 ]. Another study done in Abha investigated the prevalence of VV among school teachers of both genders and reported a high prevalence of 42%; most of them were female teachers [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Saudi Arabia, few studies described the prevalence of VV among both sexes of the population, but there were not many studies that described the association between VV and the type of occupation or the number of hours sitting or standing at work and lifestyle factors such as smoking and exercising [ 18 - 19 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Varicose veins are more common in police officers, teachers, nurses, shopkeepers, and bus conductors. As per the study done in Abha, the incidence of VV among both male and female school teachers was high (42%), with the majority in female instructors [9]. Nurses have two major risk factors for developing varicose veins: gender and prolonged standing during duty hours.…”
Section: Introductionmentioning
confidence: 87%
“…The prevalence of VV varies between 10% and 60% globally, and it is higher in Asia than in the Western world, with Saudi Arabia having a prevalence of 62% [12]. In Saudi Arabia, there were insufficient studies that delineate the association between VV and the nature of occupation or the number of hours sitting or standing at work, as well as lifestyle variables like smoking and exercising [12][13][14]. So, our aim is to assess the risk of varicose veins among teachers in Al-Ahsa, Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%